The Effect of Online and Face-to-Face Active Learning on The Students’ Social Skills in The Post-Pandemic - Pramesti, Getut (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2024)
Abstract:Online learning during the COVID-19 pandemic (SARS-CoV-2) isolated students for three years, leading to several consequences, one of which is social skills. This study compares cognitive abilities, social presence, social interaction, collaboration, and student satisfaction in online and offline learning from the perspective of gender differences among students. Social presence, social interaction, collaboration, and student satisfaction are structural components of social skills. The research employs multivariate covariance analysis with basic statistics courses as the covariate variable. The population includes all Mathematics Education students at a public university in Surakarta. The sample was obtained through random cluster sampling, specifically, second-semester students enrolled in data analysis techniques courses. The results indicate significant differences in cognitive abilities, social interaction, collaborative learning, and satisfaction between the two learning modalities. The social skills of students post-COVID-19 are unique to each gender. Abstrak:Pembelajaran daring di masa Pandemi COVID-19 (SARS-CoV-2) mengisolasi mahasiswa selama 3 tahun, menimbulkan beberapa konsekuensi, salah satunya keterampilan sosial. Penelitian ini membandingkan kemampuan kognitif, kehadiran sosial, interaksi sosial, kolaborasi, dan kepuasan siswa dalam pembelajaran online dan offline dari sudut pandang perbedaan jenis kelamin siswa. Kehadiran sosial, interaksi sosial, kolaborasi, dan kepuasan siswa merupakan bagian struktur dari ketrampilan sosial. Penelitian ini menggunakan analisis kovarian multivariat dengan matakuliah statistika dasar sebagai variabel kovariat. Populasi meliputi seluruh mahasiswa Pendidikan Matematika di perguruan tinggi negeri di Surakarta. Sampel diambil secara random cluster sampling, yaitu mahasiswa semester 2 yang mengambil mata kuliah teknik analisis data. kemampuan kognitif, interaksi sosial, pembelajaran kolaboratif, dan kepuasan pada kedua pembelajaran tersebut berbeda secara signifikan. Kemampuan sosial siswa pasca COVID-19 bersifat unik untuk setiap jenis kelamin siswa.